Cracking and strength of reinforced concrete structures in flexure strengthened with carbon fibre laminates - Valivonis, Juozas; Skuturna, Tomas (Journal of Civil Engineering and Management, 2007)
The article presents the analysis of the cracking moment and the strength of beams reinforced with external carbon fibre. Experimental research of beams strengthened in this way has been carried out. Three different methods of anchoring external reinforcement were applied to strengthen the beams. The influence of anchorage on the cracking moment and the strength of the beams has been defined. Design methods for defining the cracking moment and the strength have been presented. The design procedure for defining the cracking moment evaluates the curvilinear stress diagrams of concrete under tension and compression. The design procedure for defining the strength of the structures evaluates the stiffness of the contact between the carbon fibre and the concrete. The design results are provided. Comparative analysis of the experimental and the theoretical results has been performed.Anglies pluoštu armuotų lenkiamųjų konstrukcijų pleišėtumas ir stiprumasSantrauka. Straipsnyje analizuojamas sijų su išorine anglies pluošto armatūra plyšių susidarymo momentas ir stiprumas. Atlikti anglies pluoštu sustiprintų sijų eksperimentiniai tyrimai. Trys skirtingi išorinės armatūros inkaravimo būdai buvo pritaikyti sijoms stiprinti. Nustatyta inkaravimo įtaka plyšių susidarymo momentui ir stiprumui. Pateikti skaičiavimo metodai plyšių susidarymo momentui ir stiprumui nustatyti. Plyšių susidarymo momento skaičiavimo metodika pagrįstos kreivalinijinės tempiamojo ir gniuždomojo betono įtempių diagramos, o konstrukcijų stiprumo skaičiavimu įvertintas anglies pluošto ir betono kontakto standumas. Pateikti skaičiavimo rezultatai. Atlikta eksperimentinių ir teorinių rezultatų palyginimo analizė.Reikšminiai žodžiai: išorinė anglies pluošto armatūra, stiprinimas, plyšių susidarymo momentas, stiprumas.First Published Online: 14 Oct 2010